RESEARCH MIKROZABRUDNYUVACHIV IN R.UDY USING PASSIVE SAMPLING WATER - , Ю. Ю., Ю. І. (Municipal economy of cities. Series: «Economy science», 2013)
We study mikrozabrudnyuvachi (metals) in water r.Udy (Kharkiv region). Using standard and passive sampling. The results show that mikrozabrudnyuvachiv to determine the most effective passive sampling methods.